Psychosomatic disorders with predominantly gynecological complaints: a clinical and demographic profile study at a tertiary care center - Malhotra, Tanya; Chauhan, Nidhi; Avinash, Priya Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Psychosomatic disorders, particularly somatic symptom disorders (SSD), represent a significant challenge in clinical practice due to their complex interplay of psychological and physical symptoms. Women frequently present with unexplained gynecological symptoms, often impacting their quality of life and leading to multiple healthcare consultations. This study aims to evaluate the prevalence and symptom profile of SSD in women attending a gynecology outpatient department (OPD). Methods: A cross-sectional study was conducted over 12 months in the department of obstetrics and gynecology at the Himalayan institute of medical sciences, Dehradun. Seventy-two women aged ≥18 years with unexplained gynecological symptoms persisting for >6 months were recruited. Detailed history, clinical examination, and investigations were performed to exclude organic causes. The public health questionnaire-15 (PHQ-15) was used to assess symptom severity. Data were analyzed using SPSS version 20. Results: Out of 6000 gynecology OPD attendees, 1.2% (72 patients) were diagnosed with SSD. The most common symptoms were chronic pelvic pain (56.94%), vaginal discharge (37.5%), and lower backache (26.38%). The majority (45.83%) of patients were aged 40-59 years, and 56.9% had a normal BMI. Parity of three was most common (44.44%), and 34.72% had a history of primary education. Psychiatric comorbidities were present in 34.72%, with depression being the most frequent (13.88%). Hypothyroidism (13.88%) was the most common comorbidity. PHQ-15 scores indicated that 38.88% had moderate severity of symptoms. Conclusions: SSD is an underrecognized but significant concern among women with unexplained gynecological symptoms. Chronic pelvic pain and vaginal discharge were the most prevalent symptoms. A multidisciplinary approach, including psychiatric evaluation, is essential for effective management of these patients.